Comparing the effects of compression contrast therapy and dry needling on muscle functionality, pressure pain threshold, and perfusion after isometric fatigue in forearm muscles of combat sports athletes: A single-blind randomized controlled trial - Kuzdzal, A.; Clemente, F. M.; Kawczynski, A.; Ryszkiel, I.; Trybulski, R. (Journal of Sports Science & Medicine, 2024)
The aim of this study was to compare the acute effects of compression contrast therapy (CT) and dry needling therapy (DN) on muscle tension (MT), muscle strength (Fmax), pressure pain threshold (PPT), and perfusion (PU) following fatigue of forearm muscles (e.g., flexor carpi radialis) in combat sports athletes. A single-blind randomized controlled trial was employed. Participants first underwent muscle fatigue induction, which involved sustaining an isometric handgrip at 60% of their maximum voluntary contraction in 5-second cycles. This was followed by exposure to one of the regenerative therapies. Forty-five participants were randomly assigned to one of three groups: CT/DN (n = 15), CT/ShDN (n = 15), and ShCT/DN (n = 15). The sham condition (Sh) involved a simulated version of the technique. Measurements were taken at four time points: (i) at rest; (ii) immediately after exercise that led to a state of fatigue; (iii) 5 minutes after therapy (PostTh5min); and (iv) 24 hours after therapy (PostTh24h). Each participant was exposed to one experimental condition and one control condition, thereby undergoing evaluation in two sessions. Significant differences between groups were found in MT during the PostTh5min (p = 0.005), as well as in PU during the PostTh5min (p < 0.001) and PU during the PostTh24h (p < 0.001). All groups showed significant improvements at 5 minutes post-therapy compared to immediately post-muscle fatigue. As conclusions, CT/DN seems to be significantly better for enhancing MT and PU after 5 minutes of muscle fatigue induction. Using either CT, DN, or both combined is recommended to enhance the recovery of muscle functionality and properties, favoring recovery and potentially speeding up performance enhancement.